MEDIA PEMBELAJARAN INTERAKTIF CANDI BERSEJARAH BUDHA DAN HINDU MENGGUNAKAN ADDIE - Andi, Andi; Deli, Deli (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2023)
History is a social science that studies important events that happened in the past. Indonesia is known to have a diverse historical and cultural heritage that can be used as a learning capital. One of Indonesia's historical sites is the temple. The purpose of this study is to develop interactive learning media on the topic of temples and pagodas that can help students increase their interest in learning and improve their knowledge about temples. To develop learning materials, the researchers used the ADDIE method. The data collection technique in this study used qualitative data collection conducted through interviews and questionnaire distribution. The results of this study indicate that developed learning media can increase learning interest and are easy for students to use.